Out-group peer involvement in youth alcohol consumption - Gallage, H.P.Samanthika; Tynan, Caroline; Heath, Teresa (Wiley, 2017)
Recent studies of alcohol consumption among students have consistently linked in-group influence with excessive drinking. Concurrently, these studies have largely overlooked the influence of non-alcohol-consuming peers (the out-group) on the in-group's decisions to consume alcohol. However, out-groups can have a significant impact on in-group members' decisions regarding publicly consumed products (White, Simpson, & Argo, 2014), such as is the case of alcohol. In light of this, our study aims to explore how in-group members' views of their consumption of alcohol are influenced by their out-group. This study uses Social Identity Theory as the theoretical lens to explain consumer interaction with the out-group (abstainers) and subsequent views of in-group members (alcohol consumers). A social constructivist approach is adopted to enable this exploration of meaning, with concomitant use of the qualitative narrative methodology. A sample of 18 postgraduate students studying in the UK was selected. Narratives were collected and analysed using thematic analysis. Although the widely accepted view is that people tend to avoid products or behaviours that are linked with an out-group, this paper demonstrates conditions in which alcohol consumers appreciate the out-group. Furthermore, it reveals how drinkers' interaction with their out-group can lead to negative attitudes towards their in-group and their own consumption of alcohol. Based on their views of out-groups, we propose a categorisation of alcohol consumers into 3 groups: avoiders, open admirers, and covert admirers. Finally, we discuss the theoretical and practical implications for social marketers and policy makers.